OFR-155-83 Evaluation Of The Black River Mine Telecommunication System - Dana T. Updyke (The National Institute for Occupational Safety and Health (NIOSH), 1983)
An evaluation was made of one of several improved underground communication systems sponsored by the U.S. Bureau of Mines. The system evaluated was installed in a typical metal/non-metal room and pillar mine and utilized UHF repeaters connected to a unique distributed antenna and passive reflector system which provided mine-wide communications. A microprocessor controlled data collection system was assembled and installed for the evaluation. Data consisting principally or times and durations of messages and identities of the originating transceivers was collected between February and August of 1982 (6 mos.). Analysis of the data shows that the principal benefits are reduction in time required for unscheduled maintenance and repair, enhancement of safety, and better coordination of production activities. A cost benefit analysis shows a net benefit over cost, although it is also concluded that the capacity of the system is greater than can be justified by current activity in the mine.